Conceptualization, Development and Implementation of a Model Physical and Cognitive Geriatric Rehabilitation Program among Community-Dwelling Older Adults in Nigeria: A Study Protocol - Mannir Kassim; Naziru Bashir Mukhtar; Isa Usman Lawal; Mukadas O. Akindele; Adedapo Wasiu Awotidebe (Kwaghe International Journal of Engineering and Information Technology, 2026)
Geriatric rehabilitation provides older adults with opportunities to maintain functional independence, autonomy, and quality of life through structured physical and cognitive support. In Nigeria, community-dwelling older adults often encounter barriers to accessing rehabilitation services because of limited resources, highlighting the need for contextually appropriate and effective rehabilitation models. However, the conceptualization, development, and implementation of an integrated physical and cognitive geriatric rehabilitation program have not been empirically investigated among this population. This study protocol aims to present a comprehensive framework for designing, developing, and implementing a model physical and cognitive geriatric rehabilitation program for community-dwelling older adults in Nigeria. The study adopts an embedded mixed-methods approach comprising three sequential phases: a cross-sectional survey, a phenomenological inquiry, and a randomized controlled trial. Quantitative data will be analyzed using IBM SPSS version 25 through descriptive and inferential statistics, while frequencies and percentages will be used to summarize participants’ sociodemographic characteristics. As a protocol, the study provides a structured methodological basis for examining the feasibility and potential effectiveness of a geriatric rehabilitation model tailored to the Nigerian context. The proposed program is expected to contribute to geriatric care by supporting evidence-informed rehabilitation practices that promote physical functioning, cognitive health, autonomy, and quality of life among older adults.